Cement Compressive Strength Control Using CUSUM and MCUSUM Control Chart - Surya Puspita Sari; Ferra Yanuar; Dodi Devianto (Science and Technology Indonesia, 2020)
Compressive strength is one of the test factors used to determine whether cement production is in a controlled state or not. Portland type composite cement or PCC is the cement that is widely used in infrastructure development. The Cement of 3-days compressive strength, 7-days compressive strength, and 28-days compressive strength are the variables that will be controlled in this study. The normal distribution test and correlation test show that the data on each variable is normally distributed, and each variable has a strong correlation. Univariate cement control using the cumulative sum control chart (CUSUM) and multivariate control using a multivariate cumulative sum (MCUSUM) control chart is performed to obtain the best control results. Correlated variables show that control using a multivariate control chart results in fewer outs of control observations compared to a univariate control chart. This explains that the MCUSUM control chart is more sensitive than the CUSUM control chart in controlling observations of data out of control.